2009
DOI: 10.1016/j.ijsu.2008.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in coagulation profile and incidence of DVT in laparoscopic cholecystectomy

Abstract: CO(2) pneumoperitoneum enhances the activation of coagulation and fibrinolysis associated with laparoscopic cholecystectomy. Patients with risk factors like old age, obesity or with expected long duration of laparoscopic surgery are likely to have significant activation of coagulation, making them a vulnerable risk group for development of postoperative deep vein thrombosis, warranting some form of thromboprophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 15 publications
5
27
0
Order By: Relevance
“…27 Several investigations showed markers of postoperative hypercoagulability. [30][31][32][33][34][35][36][37] One investigation showed no hemostatic changes in blood draining the lower limbs. 38 More sizeable changes in coagulation activation were observed in the elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…27 Several investigations showed markers of postoperative hypercoagulability. [30][31][32][33][34][35][36][37] One investigation showed no hemostatic changes in blood draining the lower limbs. 38 More sizeable changes in coagulation activation were observed in the elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Long operating times remain a particular concern for the obese population, in which the risk of complications such as atrial fibrillation, pulmonary embolism, deep venous thrombosis (DVT), and rhabdomyolysis may be increased [24][25][26][27][28][29][30][31]. The risk of atrial fibrillation may be increased by 50%, whereas the reported relative risk of DVT and pulmonary embolism is as high as 3.0, increasing further for patients with a BMI greater than 40 kg/m 2 [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, concerns regarding systemic complications and pathophysiology are still being investigated [1]. …”
Section: Introductionmentioning
confidence: 99%